IITA@50 celebrations recap - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
IITA's Director for Eastern Africa gives a recap of the #IITA50 celebrations in Eastern Africa. They were held at the hub's headquarters in Dar es Salaam, Tanzania on 12 July 2017.